2021
DOI: 10.7759/cureus.15165
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Helicobacter pylori and Gastric Carcinoma

Abstract: Gastric carcinoma is the third leading cause of cancer mortality worldwide. In 2018, the incidence of gastric carcinoma worldwide was over 1,000,000 new cases, with approximately 783,000 deaths. The rate of new cases is noticeably increased in Eastern Asia. Helicobacter pylori is responsible for the increased incidence of gastric cancer. In the year 2015, H. pylori had an approximate prevalence of 4.4 billion positive cases worldwide, with the most positive cases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Like hesperidin, ponciretin has shown anticancer and anti-inflammatory effects, with cytotoxic effects on a colon cancer cell line in vitro [ 27 ] and attenuating colitis in mice by the anti-inflammatory effects of suppressing NF-κB activation and correcting the imbalance of Th17/Treg cells [ 33 , 34 ]. In addition, ponciretin can inhibit the growth of Helicobacter pylori [ 35 ], a bacterium implicated in gastritis, stomach ulcers, and lymphomas of the gastrointestinal tract [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like hesperidin, ponciretin has shown anticancer and anti-inflammatory effects, with cytotoxic effects on a colon cancer cell line in vitro [ 27 ] and attenuating colitis in mice by the anti-inflammatory effects of suppressing NF-κB activation and correcting the imbalance of Th17/Treg cells [ 33 , 34 ]. In addition, ponciretin can inhibit the growth of Helicobacter pylori [ 35 ], a bacterium implicated in gastritis, stomach ulcers, and lymphomas of the gastrointestinal tract [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et a1 13 reported that H. pylori infects more than half of the world's population and the infection is usually acquired in childhood and remains for life long. Similarly, Tiwari et al 14 mentioned that younger patients (less than 45 years) from the Indian sub-continent infected with H. pylori have higher risk of developing gastric carcinoma while, Thapa et al 4 found the common age group for the H. pylori infection in both the sexes is between 61-70 years and the infection is highly prevalent in distal gastric carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…3 The invasion and colonization of the gastric mucosa by H. pylori is strengthened by host factors, environmental factors and virulence factors like adhesion, translocation, and inflammation of the host gastric epithelium which changes the normal host immune response and cytokines to remain in the gastric epithelium for an extended period of time. 4 The human immune system identifies H. pylori as a foreign particle and provokes the inflammatory response to eradicate the bacterium from the body which induces the serious infection and may further progress to cancer. 5 The chronic infection with H. pylori bacteria is the most important risk factor for the development of non-cardia gastric cancer and lower grade B-cell mucosa associated lymphoid tissue (MALT) lymphoma estimating 6,60,000 cancer cases in the year 2008 attributed to H. pylori and corresponding to 5.2% of the total burden from all cancers globally.…”
Section: Introductionmentioning
confidence: 99%
“…Eradication of H. pylori reduces the incidence of gastric cancer [ 48 , 49 ]. Current research has shown that a variety of virulence factors produced by H. pylori , for instance, CagA, VacA, HtrA, Baba, Saba, and oipa, can help it attach to gastric epithelial cells, cause the host immune system to release various pro-inflammatory cytokines and chemokines and activate multiple signal pathways, such as the NF-κB, Wnt/β-catenin, and PI3K/Akt/mTOR pathways, which affect cell proliferation and differentiation, and promote the transformation of normal gastric epithelial cells into cancer cells [ 50 , 51 ]. In this study, we demonstrated that H. pylori increased the proliferative activity of gastric epithelial cells in a certain range, and the increased activity was positively correlated with the number of bacteria loaded.…”
Section: Discussionmentioning
confidence: 99%